Microengineered Bioartificial Liver Chip for Drug Toxicity Screening. (21st May 2018) - Delalat, Bahman; Cozzi, Chiara; Rasi Ghaemi, Soraya; Polito, Giovanni; Kriel, Frederik H.; Michl, Thomas Danny; Harding, Frances J.; Priest, Craig; Barillaro, Giuseppe; Voelcker, Nicolas H.
Abstract: Microfluidic 3D cell culture is a promising technology for the screening of drug toxicity profiles. In this study, a bioartificial liver consisting of a surface‐engineered microfluidic silicon chip with microtrenches mimicking hepatic sinusoids is shown to extend 3D primary hepatocyte culture and improve in vitro drug screening for hepatotoxicity, with respect to the state‐of‐the‐art literature on this subject. Primary hepatocytes hosted in the 3D heparin‐coated microtrenches (the bioartificial liver) secrete high levels of albumin and urea over 4 weeks. The cytotoxicity of common drugs, namely, acetaminophen, chlorpromazine, and tacrine, was assessed on primary hepatocytes both at day 1 and day 7. The results suggest that mimicking hepatic sinusoids using a microtrench format allows the maintenance of difficult‐to‐culture primary hepatocytes to be extended to 4 weeks and provides an alternative model to animal studies for the screening of the cytotoxicity of new drugs. Abstract : The liver is the focal point of numerous studies intended for better understanding the toxicological response of body to novel pharmaceutical entities. A bioartificial liver that supports long‐term primary hepatocyte culture in 3D heparin‐coated microtrenches mimicking the architecture of hepatic sinusoids is developed and tested as predictive in vitro model for hepatotoxicity screening.